Why the need to triangulate in the study of tourism's economic impact - Chong, Yee Lee; Lee, Eng Heng; Ramachandran, Sridar; Yacob, Mohd Rusli; Othman, Mohhidin (IDOSI Publications, 2011)
Over the years, Input-Output (I-O) analysis has been popularly used for measuring the economic impact of tourism; but discussions in the literature of data collection methods have not been as prevalent as the discussions of empirical results and ways of modifying the basic I-O model. Due to its strong attachment to the economic multiplier concept, positivism paradigm has been preferred by researchers for estimating the spin-off effects that arise from the tourist expenditure in a region’s economy. However, quantitative data obtained from tourism establishments and secondary sources may not be accurate - for example, is the tourism establishment proprietors’ estimation of tourist count reliable? This paper suggests the use of triangulation method (including qualitative technique) to cross-check data collected from quantitative technique, so that a researcher can hope to overcome the weakness or intrinsic biases and problems that can emerge from a single-method or single-observer or single-theory study. Overall, the quality of the triangulation’s outcome depends to a great extent on how systematic the researcher is in analyzing qualitative material and his or her ability to justify the role of mixed methods in the research.